Extending 'Kampuchea' guava shelf-life at 27°C using 1-methylcyclopropene - Ding, Phebe; Ong, P. T. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
'Kampuchea' guavas were treated with 300, 600 and 900 nL L-1 1-methylcyclopropene (1-MCP) for 0, 3 and 6 h, and stored at 27°C with 70% relative humidity. The C* values, soluble solids concentration, titratable acidity and pH of these fruits were not affected by both the 1-MCP concentrations and exposure duration while h° values and flesh firmness were affected by these treatments. The L* values, vitamin C content and weight loss were affected by the concentrations of 1-MCP, but not by the exposure duration. Less weight loss and disease incidence in fruit treated with 600 and 900 nL L-1 1-MCP. Fruit exposed to 6 h 1-MCP showed lowest disease incidence compared to other exposure duration in 5 days of storage. Treating Kampuchea guava fruit with 600 nL L-1 1-MCP and exposure duration of 6 h was able to retain fruit colour, flesh firmness and delayed disease development for 5 days.